Genomewide association study on monoclonal gammopathy of unknown significance (MGUS) - Thomsen, Hauke; Weinhold, Niels; Goldschmidt, Hartmut; Hemminki, Kari; Försti, Asta (European journal of haematology, 2017)
Objectives: To identify germ line variants contributing to the development of monoclonal gammopathy of undetermined significance (MGUS), an asymptomatic premalignant precursor for multiple myeloma (MM). Methods: We conducted the first genomewide association study (GWAS) on MGUS on 243 German cases with a replication on 294 Czech cases. Identified loci were further analyzed in 1508 German MM patients. New MM loci recently reported in a meta-analysis were also tested in the MGUS GWAS. Results: In GWAS, we identified 10 loci contributing to development of MGUS at P-value threshold of 10−5. The Czech cohort gave support for two associations (6q26, rs6933936; 7p21.3 rs10251201). In GWAS, rs974120 (8p23.2) reached genomewide significance (P=2.94×10−9), with a nominal significance in MM. The locus of rs974120 shows marks of transcriptional activity in leukemia according to ENCODE data. rs10251201 (7p21.3), rs9318227 (13q22.1), and rs10405859 (19q13.32) were associated with markers related to leukemogenesis and immune and inflammatory responses. Two newly identified candidate loci for MM, rs1948915 (8q24.21) and rs8058578 (16p11.2), were nominally associated with MGUS. Conclusions: These data allow a cautious first proposal for a germ line architecture of MGUS with links to leukemia and autoimmune conditions, the latter agreeing with a family study showing clustering of MGUS with autoimmune diseases.